Diagnostics of Environmental and Social Threats to the Territory’s Development - Hkilchenko, Natalia Vasilevna; Atamanova, Elena Aleksandrovna; Slavikovskaya, Yuliia Olegovna (Economy of Regions, 2020)
The article substantiates the need for integrated diagnostics of air quality. Such diagnostics shoidd include the generally accepted indicators and consider the rate of child populations morbidity with respiratory diseases, recognized by the World Health Organisation, as a criterion for assessing the state of the atmosphere in this area. We suggest a method of integrated assessment of the level and changes in air quality over time on the considered territory. This tool allows determining the ratings of the regions on the quality of atmospheric air, the level of environmental development and the degree of its change. Moreover, it helps assessing the factors that affect the aforementioned processes. We tested the proposed methodological tools on the example of the regions of the Ural Federal district (UFD) and the Russian Federation (RF) in general. The calculations made it possible to diagnose the stabilization of environmental and social threats to air quality in the majority of the regions. We concluded that the threats caused by air pollution are increasing. That fact is confirmed by the growth of child morbidity in all regions of the UFD and the RF, except for Fyumen oblast. We propose methodological tools for diagnostics of the territory’s environmental development through integrated comprehensive indices of the state and level of environmental development in part of the air and water protection activities based on statistical indicators. The diagnostics demonstrated positive environmental development in the sphere of air protection in the UFD and the RF. In general, the dynamics of environmental development in the field of water protection are positive, with the exception of Khanty-Mansi Autonomous Okrug. The mostly positive dynamics of environmental development in the regions of the UFD are a prerequisite for reducing threats in the future.